CIDER PRODUCTION FROM APPLE VARIETY EVA AND FOUR TYPES OF ALCOHOLIC YEAST - Brunelli, Luciana Trevisan; Imaizumi, Vitor Massami; Breda, Marcelo Henrique; Venturini Filho, Waldemar Gastoni (ENERGIA NA AGRICULTURA, 2017)
The aim of this study was to produce cider from apple variety Eva, using four types of alcoholic yeast and analyze them physicochemical and sensory. The yeast used in the fermentation process were baker's yeast; high fermentation beer yeast; white wine yeast and red wine yeast. Post-fermentation sugar correction was made (<20 g L-1, 50 g L-1 and 100 g L-1) for the preparation of dry and sweet ciders. The experimental design was composed by twelve treatments. The tests were conducted with two replicates. The fruits were washed, crushed in a hammer mill and pressed to extract juice which was inoculated with four yeast strains. Fermentation process was held in PVC fermenters with capacity of 20 liters, at temperature of 18°C until the limit attenuation. After this phase, beverage transfer was made for 4.5 liters bottles, with removal of atmospheric air. Maturation process was held at temperature of 10°C for 30 days. The aged beverage had its sugar content adjusted according to the treatment and then put in 660 ml glass bottles. The cider was chemically analyzed for alcohol content, total acidity, volatile acidity, fixed acidity, turbidity and color. The four types of yeasts (baker’s, beer, red wine and white wine) interfered with the physicochemical parameters of dry ciders (<20 g L-1) and sweets (50 g L-1 and 100 g L-1). The beverages produced with white wine yeast had lower turbidity and higher total acidity. Samples produced with white wine yeast presented higher sensory quality in all parameters, such as aspect, aroma, flavor, overall assessment. The ciders produced in this study were within the standards set by Brazilian law.